2015
DOI: 10.1002/pon.3910
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spiritual interventions addressing existential themes using a narrative approach on quality of life of cancer patients: a systematic review and meta‐analysis

Abstract: Directly after the intervention, spiritual interventions had a moderate beneficial effect in terms of improving quality of life of cancer patients compared with that of a control group. No evidence was found that the interventions maintained this effect up to 3-6 months after the intervention. Further research is needed to understand how spiritual interventions could contribute to a long-term effect of increasing or maintaining quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 50 publications
(53 reference statements)
3
51
2
5
Order By: Relevance
“…However, in 2016, Kruizinga et al evaluated the effect of spiritual interventions on the quality of life in patients with cancer, focusing on literature published up to 2014. Based on 12 clinical trials, the researchers found that narrative spiritual interventions can improve the quality of life in cancer patients in the short term, but no evidence was found that this effect was maintained in the long term, up to three–six months [29]. …”
Section: Introductionmentioning
confidence: 99%
“…However, in 2016, Kruizinga et al evaluated the effect of spiritual interventions on the quality of life in patients with cancer, focusing on literature published up to 2014. Based on 12 clinical trials, the researchers found that narrative spiritual interventions can improve the quality of life in cancer patients in the short term, but no evidence was found that this effect was maintained in the long term, up to three–six months [29]. …”
Section: Introductionmentioning
confidence: 99%
“…However, since the existential and moral questions caused by a life-threatening disease such as cancer go to the very subject matter of philosophy, a different approach to cancer survivor care is intriguing to explore on its own. This different approach is supported by studies showing how both advanced cancer patients and long-term survivors report that their existential needs are insufficiently met (Kruizinga et al, 2016;Hodgkinson et al, 2006). Philosophy, particularly in its ancient form, is concerned with the art of living (Hadot, 1995;Nehamas, 2000;Sellars, 2003) and the attainment of flourishing human lives (Nussbaum, 1994).…”
Section: Introductionmentioning
confidence: 85%
“…Thirdly, participation in SDG punctured the solitude felt by most of the cancer patients. Though other interventions that involve groups (Kroenke et al, 2014;Kruizinga et al, 2016) can address the last point, the other two features define what distinguishes a philosophical approach. The first two points corresponds to the overall benefit asked in question 1 but they are visible throughout most of the responses to the other questions in the questionnaire.…”
Section: The Potential Of Sdg In Cancer Survivor Carementioning
confidence: 99%
“…Integrating advanced cancer in one's narrative of life, however, is challenging, and feelings of hopelessness, depression, and even the desire for a hastened death were found to be common among patients with advanced cancer . Therefore, care for patients with advanced cancer needs to address psychosocial, spiritual and existential health in addition to physical health . Despite improvements in cancer care in developed countries, these nonphysical domains remain largely unattended …”
Section: Introductionmentioning
confidence: 99%